A comparative report of health care provision in prisons in Poland, Hungary and the Czech Republic - MacDonald, Morag (HEUNI papers, 2003)
This report is a follow up to previous visits to the Hungarian, Polish and Czech Prison Departments in January 2001. In the first visits, discussions were held with the Prison Service Headquarters in each country about the key issues affecting the provisions of health care and related issues in the organisation and management of the prison system (see previous report, MacDonald, 2001). The initial exploratory visits also provided an understanding and knowledge of the policies for health and drug and alcohol addiction developed by the prison services in each of the countries. The initial visits of 2001 provided the basis for the second visits during 2002. The aim of the visits was to facilitate a broad-based review of provision of health care and response to drug addiction in each of the sample prisons. In each country, three prisons were visited which included male and female prisons, those for sentenced and pre-sentenced prisoners and institutions for young offenders. The sample prisons visited in the Czech Republic were Plzen male pre-sentenced and sentenced prison, Svetla nad Sazavou Women’s prison and Vsehrdy juvenile prison. In Hungary they were Kalocsa women’s prison, Szeged high-security male sentenced prison and Tököl juvenile prison. In Poland they were Katowice sentenced prison, Grochow pre-sentenced prison and Lubliniec women’s prison.